Identification of two point mutations associated with inherited antithrombin deficiency - Shiue-Wei Lai; Chia-Yau Chang; Hwei-Jen Lee; Yeu-Chin Chen (Thrombosis Journal)
Abstract Background Antithrombin (AT) is a serine protease inhibitor which exerts its anticoagulant effect through binding to serine residues in the active centers of procoagulant serine proteases. Its deficiency is associated with increased risk of venous thrombosis. We aim to investigate the pathogenic mechanism of two natural mutants (W221C and M284R) in inherited AT deficiency. Methods We analyzed 9 unrelated patients with inherited AT deficiency by extracting peripheral blood DNA and sequencing the SERPINC1 gene after amplification by polymerase chain reaction. Enzyme-linked immunosorbent assay and heparin affinity chromatography were used to assess AT secretion and purification efficiency. The mutant AT models were evaluated via computational simulations. Results Among the 9 patients with inherited AT deficiency, 8 patients had type I AT deficiency, and one patient had type II AT deficiency with subtype of reactive site mutation. Seven of them experienced venous thrombotic events and all patients were found genetic mutations including missense (n = 6), deletion (n = 2) and insertion (n = 1). Two point mutations, W221C and M284R, were identified and were hypothesized to affect AT by destabilizing the central β-sheet. Based on immunoassays and heparin purification, the W221C mutant may impair AT secretion, whereas M284R mutant decreased the total AT production (696.8 ± 151.6 ng/ml versus 3833.72 ± 315.4 ng/ml, p = 0.029). Both mutants delayed the peak of AT release in heparin affinity chromatography. Conclusions Our study demonstrates that two mutations in SERPINC1 gene altered the production and structure of AT by in vitro protein expression and functional studies, including protein secretion and production. These findings enhance our understanding of the genetic basis of AT deficiency and its possible clinical implications.